Fisiologia e Estética: elementos de uma antropologia em Diderot - Alves Junior, José Carlos (Universidade Federal de São Carlos, 2018)
This study analyzes the relationships between physiology and aesthetics in some of Diderot's works, deeming itself certain elements of an anthropology. The proposal consists in investigating how these relationships are characterized by complex operations concerning the sensitive perceptions, in which the scopes of sciences and arts intertwine. In this perspective, the study sought to examine the way by which Diderot develops an aesthetics-philosophical thought relating the physical instance to the psychic, moreover, presenting a physiological conception of the sensations which emphasize the notions of harmony and internal order as operator elements amid the concept of fine-arts. In order to explain these psycho-physiological operations, Diderot reappraises the notions of nature, science, and art following an investigative approach made possible by the advances of the medical and natural sciences, somehow distancing himself from mechanistic assumptions of that time. For this purpose, Diderot elaborates some reflections from precise elements which are obtained in the field of the arts, although finds them in analogies, metaphors, hypotheses, and conjectures that are extracted from the scientific scope. Thus, those procedures evidence the complex phenomena that compose the cerebral activities, as well as indicating certain interactions between the nervous system and some specific organs. In such investigative paths, a tension is found between the psycho-physical constitution and life in society, consequently revealing a dramatic aspect of the human existence inscribed in the boundaries of the imaginary and the experience.
Physiology and Aesthetics: elements of an anthropology in Diderot
Keywords: Diderot; Fisiologia; Estética; Ciências; Artes; Physiology; Aesthetics; Sciences; Arts; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA